Venous thromboembolism in patients with glioblastoma multiforme: Findings of the RIETE registry. Issue 6 (December 2015) - Portillo, Jose; de la Rocha, Iris Violeta; Font, Llorenç; Braester, Andrei; Madridano, Olga; Peromingo, José Antonio Díaz; Apollonio, Alessandro; Pagán, Barbara; Bascuñana, José; Monreal, Manuel; ,
Abstract: Background: There is uncertainty about the optimal therapy of venous thromboembolism (VTE) in patients with glioblastoma multiforme (GBM). Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to compare the rate of VTE recurrences and major bleeding during the course of anticoagulation in patients with GBM, other cancers and in patients without cancer. Results: As of September 2014, 53, 546 patients have been recruited in RIETE. Of these, 72 (0.13%) had GBM and 11, 811 (22%) had other cancers. Most patients in all 3 subgroups received initial therapy with low-molecular-weight heparin (LMWH), but those with GBM received slightly lower doses than those with other cancers or without cancer. Then, most patients with GBM continued on LMWH for long-term therapy, at similar doses than those in the other subgroups. During the course of anticoagulation (mean, 202 days), 3 patients with GBM presented VTE recurrences (10.9 per 100 patient-years; 95% CI: 2.76–29.5) and 4 suffered major bleeding (one intracranial) (14.5 bleeds per 100 patient-years; 95%CI: 4.60–34.9). Compared with patients with other cancers, those with GBM had a similar rate of VTE recurrences and major bleeds, but had a higher rate of extracranial hematoma (p < 0.05). Compared with VTE patients without cancer, those with GBM had a higher rate of PE recurrences (p < 0.01) and major bleeding (p < 0.001), particularly extracranial hematoma (p < 0.001). Conclusions: Patients with GBM and VTE had a similar rate of VTE recurrences or major bleeds during the course of anticoagulant therapy than those with other cancers. Highlights: The optimal therapy of VTE in patients with glioblastoma multiforme is unknown. They had a higher rate of recurrent PE and major bleeding than those without cancer. Their outcome was similar to that in patients with other cancers.